Iron-Regulated Reactive Oxygen Species Production and Programmed Cell Death in Chronic Obstructive Pulmonary Disease - Kenji Mizumura; Yasuhiro Gon (MDPI AG, 2021)
Chronic obstructive pulmonary disease (COPD) is characterized by persistent respiratory symptoms and airflow limitation. However, the pathogenesis of COPD remains unclear. Currently, it is known to involve the loss of alveolar surface area (emphysema) and airway inflammation (bronchitis), primarily due to exposure to cigarette smoke (CS). CS causes epithelial cell death, resulting in pulmonary emphysema. Moreover, CS induces iron accumulation in the mitochondria and cytosol, resulting in programmed cell death. Although apoptosis has long been investigated as the sole form of programmed cell death in COPD, accumulating evidence indicates that a regulated form of necrosis, called necroptosis, and a unique iron-dependent form of non-apoptotic cell death, called ferroptosis, is implicated in the pathogenesis of COPD. Iron metabolism plays a key role in producing reactive oxygen species (ROS), including mitochondrial ROS and lipid peroxidation end-products, and activating both necroptosis and ferroptosis. This review outlines recent studies exploring CS-mediated iron metabolism and ROS production, along with the regulation of programmed cell death in COPD. Elucidating the mechanisms of these pathways may provide novel therapeutic targets for COPD.